Interdisciplinary perspectives of rehabilitation in adult brachial plexus palsies : - (Balneo and PRM Research Journal, 2022)
The aim of this study is to demonstrate that the interdisciplinary approach could have a positive result on the rehabilitation program in brachial plexus paralysis in adults. The prevalence of brachial plexus injuries is currently increasing worldwide, mainly due to the growing number of car accidents, extreme sports or work-related injuries. In this study we chose to present an analysis of one complex surgical case of brachial plexus paralysis, with clinical and electrophysiological investigations. (1) Background: Current reconstructive surgical nerve transfer procedures aim to rehabilitate elbow flexion in such cases. Surgical strategies are based not only on clinical evaluation or investigations by magnetic resonance imaging, but also on classical electrophysiological methods, such as electromyography (EMG). (2) Methods: Along with the other types of therapies already established, in the case of this pathology, Transcranial Magnetic Stimulation (TMS) is also used, which provides valuable information about cortical reorganization models concomitant with surgical procedures for nerve reconstruction in the last 3 decades. (3) Results: The study shows that interdisciplinary leads to a faster and more complex rehabilitation of the patient with brachial plexus paralysis and thatelectrophysiological signals could predict constant motor benefits when associated with rehabilitation programs.